Investigating a shared-dialect effect between raters and candidates in English speaking tests - Xu, Ying; Huang, Mengjia; Chen, Jin; Zhang, Yaqing (Frontiers in Psychology, 2023)
This study set out to examine existence of a shared-dialect effect, a phenomenon that when a rater shares the same dialect with a candidate, the rater is more likely to give the candidate a higher score in English speaking tests. Ten Cantonese-speaking raters and ten Mandarin-speaking raters were selected to assess forty Cantonese-accented and forty Mandarin-accented candidates’ oral performance in the retelling task of the Computer-based English Listening and Speaking Test (CELST). Besides, seven raters from each group participated in the stimulated recall stage aiming to reveal their thought process. Quantitative results suggested that the two rater groups were comparable in terms of internal consistency. There were no significant differences in the scores of both candidate groups awarded by both rater groups. The effect of interaction between candidates’ dialect and raters’ dialect was not statistically significant, indicating non-existence of such effect. Qualitative results showed that some raters attended to candidates’ accents, and indicated that awareness of accents and their familiarity with the accents affected their comprehension of the speech samples and potentially influenced their scoring process. The findings are discussed with reference to rater training, rating scale, raters’ familiarity with candidates’ accents, raters’ attitudes toward candidates’ accents and the task type. The main implication of this study is that recruiting both group raters in domestic English speaking tests is warranted if the shared-dialect effect could be duly managed.